2014
DOI: 10.5604/12321966.1129933
|View full text |Cite
|
Sign up to set email alerts
|

Quality of life and occurrence of depression under chemotherapy in patients suffering from lung carcinoma

Abstract: Depression symptoms occur more frequently and with greater intensity in patients suffering from lung neoplasm, compared to the group of healthy people (p<0.01). A statistically significant connection between marital status, place of residence, and assessment of quality of life was found out (p<0.05).

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
4
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(5 citation statements)
references
References 10 publications
1
4
0
Order By: Relevance
“…Our study found that 130 of 297 patients with lung cancer had depression with a prevalence of 43.77%, similar to previous studies (Gu et al, 2017) but lower than the study carried out by Baczewska et al (2014). The reason might be that the evaluation tools used were different, and the diagnostic gold standard was lacking, which led to the different prevalence rates in an existing study.…”
Section: Discussionsupporting
confidence: 90%
See 1 more Smart Citation
“…Our study found that 130 of 297 patients with lung cancer had depression with a prevalence of 43.77%, similar to previous studies (Gu et al, 2017) but lower than the study carried out by Baczewska et al (2014). The reason might be that the evaluation tools used were different, and the diagnostic gold standard was lacking, which led to the different prevalence rates in an existing study.…”
Section: Discussionsupporting
confidence: 90%
“…These patients also report unpleasant physical and emotional stresses, such as decreased physical function, fatigue, pain and depression (Medysky et al, 2021). Depression is pervasive and popular in patients with lung cancer (Wang et al, 2022), with an incidence ranging from 19% to 73.9% (Baczewska et al, 2014; Liu et al, 2018; Park et al, 2016). Depression caused by lung cancer is characterised by refractory, high recurrence rate, and multi‐factorial pathogenesis, which has become an essential reason for reducing patients' clinical therapeutic efficacy and quality of life and even leading to adverse health outcomes such as increasing the risk of suicide (Gu et al, 2017; Liu et al, 2022; Santos, 2017).…”
Section: Introductionmentioning
confidence: 99%
“… 12 In the questions regarding QOL, the answers are graded on the scale of 1-7, with the ascending values indicating increasing QOL. 6 To facilitate the analysis, the points were standardized on the scale of 1 to 100 and assessed according to a 4-degree Likert scale, namely, 0–25 points indicated “very low QOL,” 26–50 points indicated “low QOL,” 51–75 points indicated “high QOL,” and 76–100 points indicated “very high QOL. 6 …”
Section: Methodsmentioning
confidence: 99%
“… 3 The severity of cancer-related symptoms has been strongly related to the psychological symptoms in the patients, 4 and the unhealthy psychological status has been shown to be associated with a significantly increased frequency of cancer-related mortality. 5 Of 102 lung cancer patients treated by chemotherapy, Baczewska found 6 that 51.5% showed symptoms of severe depression, suggesting that depression occurs more frequently and with greater intensity in lung cancer patients as compared with that in healthy individuals. In another study of 1334 consecutively recruited lung cancer patients, Shimizu 7 reported 440 with significant anxiety issues.…”
mentioning
confidence: 99%
“…As can be seen from the literature review, quality of life is an issue investigated by many researchers, some of whom have done so during chemotherapy [6], radiotherapy and other treatments, such bone marrow transplants [7]. Others referred to quality of life in specific types of cancer (breast, lung, prostate) [8].…”
mentioning
confidence: 99%